Oral trans-mucosal dexmedetomidine for controlling of emergence agitation in children undergoing tonsillectomy: a randomized controlled trial - Abdel-Ghaffar,Hala S. (2019)
Abstract Objectives: Emergence agitation is a negative behavior commonly recorded after pediatric tonsillectomy. We investigated the efficacy of preoperative premedication with oral transmucosal buccal dexmedetomidine on the incidence and severity of emergence agitation in preschool children undergoing tonsillectomy under sevoflurane anesthesia. Methods: Ninety patients aged (3–6 years), ASA I‒II were enrolled into three groups (n = 30) to receive oral transmucosal dexmedetomidine 0.5 µg.kg-1 (Group DEX I), 1 µg.kg-1 (Group DEX II) or saline placebo (Group C). Our primary endpoint was the Watcha agitation score at emergence in PACU. Secondary outcomes were preoperative sedation score, intraoperative hemodynamics, postoperative Objective Pain Scale (OPS) and adverse effects. Results: The patients’ demographics, preoperative sedation scores and extubation time showed no difference between groups. Significant differences between groups in incidence and frequency distribution of each grade of Watcha score were evident at 5 minutes (p= 0.007), 10 minutes (p= 0.034), 30 minutes (p= 0.022), 45 minutes (p= 0.034) and 60 minutes (p= 0.026), postoperatively with significant differences between DEX I and II groups. DEX groups showed lower OPS scores at 5 minutes (p= 0.011), 10 minutes (p= 0.037) and 30 minutes (p= 0.044) after arrival at PACU, with no difference between DEX I and II groups. Patients in DEX II group exhibited lower intraoperative mean heart rate at 15 min (p= 0.020), and lower mean arterial pressure at 30 minutes, (p= 0.040), 45 minutes (p= 0.002) and 60 minutes (p= 0.006) with no significant differences between groups in other time points. Conclusion: This study demonstrates the clinical advantage and the simple technique of oral transmucosal DEX premedication for emergence agitation in preschool children undergoing tonsillectomy under sevoflurane anesthesia compared with saline placebo. Trial registration Clinical Trials.gov trial registry: NCT02720705.